The Influence of the Consumer Ethnocentrism and Cultural Familiarity on Brand Preference: Evidence of Event-Related Potential (ERP) - Ma, Qingguo; Abdeljelil, H’meidatt Mohamed; Hu, Linfeng (Frontiers in Human Neuroscience, 2019)
The tendency of customers’ preference to their local brands over the foreign ones is known as the consumer ethnocentrism, and it is one of the important issues in international marketing. This study aims at identifying the behavioral and neural correlates of Consumer Ethnocentrism in the field of brand preference by using Event-Related Potential (ERP). We sampled subjects from two ethnic groups, the Chinese ethnic group and the sub-Sahara black Africans group from the Zhejiang University. The subjects faced two sequential stimuli, S1 followed by S2. The S1 consisted of 40 pictures of 20 Chinese and 20 Africans black peoples wearing traditional clothes, and S2 consisted of 40 fake brand-logos which were divided randomly into two groups of 20 each. The subjects were informed that the people in the S1 purchased and recommended the products with the brand-logos presented in S2, and the subjects were asked to rate their preference degree toward these logos. The brand-logos were called the “in-group recommended logos” if the recommender in S1 were the same race as the subjects, otherwise, the “out-group recommended logos”.The results revealed that the race of the brand-logo recommender highly impacted the Chinese subjects’ preference for the brand-logos. The N200 component elicited by in-group recommended logos were significantly lower than those elicited by out-group recommended logos. Besides, there was evidence that being familiar with foreign cultures reduces consumer ethnocentrism. The African subjects were familiar with Chinese people and adopted Chinese culture, as a result, they did not differ in showing preferences between in-group and out-group recommended logos.